Chinese Female Consumer Motivation Towards Luxury Fashion Products Purchase : Differences between Generation Y & X - Zhang, Hao Ran (2014)
Purpose – There have been quite a number of researches in the luxury consumption field, but few studies has paid its attention to the key motivations in female Chinese consumers, not to mention from the perspective of different age cohorts. Therefore, in this study, the researcher focuses the different age cohorts in Chinese female consumers to find out the insights in regard to the luxury fashion products purchasing. Methodology – The researcher used Means Ranking, Two independent sample T-test and Factor Analysis in order to accomplish the objectives in this study. A method snowball sampling is applied for the data collection. Findings – The results indicate that, overall, Chinese female consumers nowadays attach more importance into the personal level. Also, experiential and functional aspects of luxury fashion products purchase is closely linked to the purchasing motivation. Practical Implications – This study offers new empirical support for the proposition that there is a tendency of shifting from China’s consuming culture to Western society’s consuming culture. Additionally, it suggests that, conspicuous consumption, what have been previously believed in western conceptualizations is the form of luxury products consumption in China needs to be re-evaluated. Originality – This research offers new empirical findings that are helpful to a re-conceptualization of Chinese female generation Y&X in luxury fashion products consumption. Particularly, the research provides the differences of Chinese female consumers in luxury fashion products consumption based on different age cohorts.